Q: What are G F Bernhard Riemann Achievements?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

This is impossible to give as a fact as everybody will have a different opinion. the top ten is 1. Leonhard Euler 2. Carl Friedrich Gauss 3. G. F. Bernhard Riemann 4. Euclid 5. René Descartes 6. Alan Turing 7. Leonardo Pisano Blgollo (a.k.a. Leonardo Fibonacci) 8. Isaac Newton and Wilhelm Leibniz 9. Andrew Wiles 10. Pythagoras

Assume f=f(x), g=g(x)and (f^-1)(x) is the functional inverse of f(x). (f+g)'=f'+g' (f*g)'=f'*g+f*g' product rule (f(g))'=g'*f'(g) compositional rule (f/g)'=(f'*g-f*g')/(g^2) quotient rule (d/dx)(x^r)=r*x^(r-1) power rule and applies for ALL r. where g^2 is g*g not g(g)

PIERRE DE FERMAT's last Theorem. (x,y,z,n) belong ( N+ )^4.. n>2. (a) belong Z F is function of ( a.) F(a)=[a(a+1)/2]^2 F(0)=0 and F(-1)=0. Consider two equations F(z)=F(x)+F(y) F(z-1)=F(x-1)+F(y-1) We have a string inference F(z)=F(x)+F(y) equivalent F(z-1)=F(x-1)+F(y-1) F(z)=F(x)+F(y) infer F(z-1)=F(x-1)+F(y-1) F(z-x-1)=F(x-x-1)+F(y-x-1) infer F(z-x-2)=F(x-x-2)+F(y-x-2) we see F(z-x-1)=F(x-x-1)+F(y-x-1 ) F(z-x-1)=F(-1)+F(y-x-1 ) F(z-x-1)=0+F(y-x-1 ) give z=y and F(z-x-2)=F(x-x-2)+F(y-x-2) F(z-x-2)=F(-2)+F(y-x-2) F(z-x-2)=1+F(y-x-2) give z=/=y. So F(z-x-1)=F(x-x-1)+F(y-x-1) don't infer F(z-x-2)=F(x-x-2)+F(y-x-2) So F(z)=F(x)+F(y) don't infer F(z-1)=F(x-1)+F(y-1) So F(z)=F(x)+F(y) is not equivalent F(z-1)=F(x-1)+F(y-1) So have two cases. [F(x)+F(y)] = F(z) and F(x-1)+F(y-1)]=/=F(z-1) or vice versa So [F(x)+F(y)]-[F(x-1)+F(y-1)]=/=F(z)-F(z-1). Or F(x)-F(x-1)+F(y)-F(y-1)=/=F(z)-F(z-1). We have F(x)-F(x-1) =[x(x+1)/2]^2 - [(x-1)x/2]^2. =(x^4+2x^3+x^2/4) - (x^4-2x^3+x^2/4). =x^3. F(y)-F(y-1) =y^3. F(z)-F(z-1) =z^3. So x^3+y^3=/=z^3. n>2. .Similar. We have a string inference G(z)*F(z)=G(x)*F(x)+G(y)*F(y) equivalent G(z)*F(z-1)=G(x)*F(x-1)+G(y)*F(y-1) G(z)*F(z)=G(x)*F(x)+G(y)*F(y) infer G(z)*F(z-1)=G(x)*F(x-1)+G(y)*F(y-1) G(z)*F(z-x-1)=G(x)*F(x-x-1)+G(y-x-1)*F(y) infer G(z)*F(z-x-2)=G(x)*F(x-x-2)+G(y)*F(y-x-2) we see G(z)*F(z-x-1)=G(x)*F(x-x-1)+G(y)*F(y-x-1 ) G(z)*F(z-x-1)=G(x)*F(-1)+G(y)*F(y-x-1 ) G(z)*F(z-x-1)=0+G(y)*F(y-x-1 ) give z=y. and G(z)*F(z-x-2)=G(x)*F(x-x-2)+G(y)*F(y-x-2) G(z)*F(z-x-2)=G(x)*F(-2)+G(y)*F(y-x-2) G(z)*F(z-x-2)=G(x)+G(y)*F(y-x-2) x>0 infer G(x)>0. give z=/=y. So G(z)*F(z-x-1)=G(x)*F(x-x-1)+G(y-x-1)*F(y) don't infer G(z)*F(z-x-2)=G(x)*F(x-x-2)+G(y)*F(y-x-2) So G(z)*F(z)=G(x)*F(x)+G(y)*F(y) don't infer G(z)*F(z-1)=G(x)*F(x-1)+G(y)*F(y-1) So G(z)*F(z)=G(x)*F(x)+G(y)*F(y) is not equiivalent G(z)*F(z-1)=G(x)*F(x-1)+G(y)*F(y-1) So have two cases [G(x)*F(x)+G(y)*F(y)]=G(z)*F(z) and [ G(x)*F(x-1)+G(y)*F(y-1)]=/=G(z-1)*F(z-1) or vice versa. So [G(x)*F(x)+G(y)*F(y)] - [ G(x)*F(x-1)+G(y)*F(y-1)]=/=G(z)*[F(z)-F(z-1)]. Or G(x)*[F(x) - F(x-1)] + G(y)*[F(y)-F(y-1)]=/=G(z)*[F(z)-F(z-1).] We have x^n=G(x)*[F(x)-F(x-1) ] y^n=G(y)*[F(y)-F(y-1) ] z^n=G(z)*[F(z)-F(z-1) ] So x^n+y^n=/=z^n Happy&Peace. Trần Tấn Cường.

The product rule for derivatives is as follows. For the derivative of the product of two functions, "f" and "g":(f times g)' = f times g' + f' times g

To find f(g(-2)), we need to substitute -2 into g(x) first. Thus, g(-2) = 22 - 1 = 21. Now, we can substitute g(-2) = 21 into f(x). So, f(g(-2)) = f(21) = 4(21) + 5 = 89. Therefore, f(g(-2)) is equal to 89.

Related questions

dont no

G. Riemann has written: 'Die taubstumm-blinden' -- subject(s): Blind, Deaf, Education

Bernhard Gaudian goes by Bernie G.

a-g-f-f-f-f-f-f-f-g-a-g-a-g-f-f-f-f-f-f-f-f-f-a-g-g-a-g-f-f-g-a-a-a-a-a-a-g-f

Bernhard G. Funck has written: 'Konflikte im Steuerrecht' -- subject(s): Taxation, Law and legislation, Tax administration and procedure

a-g-f-f-f-f-f-f-f-g-a-g-a-g-f-f-f-f-f-f-f-f-f-a-g-g-a-g-f-f-g-a-a-a-a-a-a-g-f that is only chorus

Baby by: Justin BieberF G F F A G F E D E D F A G F E D E D F A G F G G F EF C2 A G A F C2 A G F C2 A G A F C2 A G F C2 C2 A G F C2 C2 A GF F A G A G A G A G A G F C2 A G A C2 A G F C2 G A F F G F F F A A G F GF F G G G G G G A G F F G FChorus: A G A G A G C2 G A G A G A G D2 G A G A G A G C2 A G A A A G FA G A G A G C2 G A G A G A G D2 G A G A G A G C2 A G A A A G F-Rossele-Send more requests @ycel_gandah@Yahoo.comTy!

C g g f g f c c d d c d f g a g f c c g f d c g g f g f c d d c d f g c c a g f c a g d f a g f c a g f g c f e d c e d c d f a g f d d f a g c d f f a g f d f g c g g f g f c c d d c d f g a g f c a g f d c g g f g f c d d c d f g c c a g f c a g d f a g f c a g f g c f e d c e d c d f a g f d d f a g c d f f a g f d f g c g f g f g f c c d f c d f c g g-f g-f g-a-f c d f c d f c g g-f g-f g-f-d c d f c d f c g g-f g-f g-a-f

Baby by: Justin BieberF G F F A G F E D E D F A G F E D E D F A G F G G F EF C2 A G A F C2 A G F C2 A G A F C2 A G F C2 C2 A G F C2 C2 A GF F A G A G A G A G A G F C2 A G A C2 A G F C2 G A F F G F F F A A G F GF F G G G G G G A G F F G FChorus: A G A G A G C2 G A G A G A G D2 G A G A G A G C2 A G A A A G FA G A G A G C2 G A G A G A G D2 G A G A G A G C2 A G A A A G F-Rossele-Send more requests @ycel_gandah@yahoo.comTy!

C c f g ac f g a g f g ff f g a g b a f g fc f g ac f g a g f f g ff f g a g b a f g f

right hand:E G F G F G G G G G G G G Left hand G F F F F F G F F F E E

This is impossible to give as a fact as everybody will have a different opinion. the top ten is 1. Leonhard Euler 2. Carl Friedrich Gauss 3. G. F. Bernhard Riemann 4. Euclid 5. René Descartes 6. Alan Turing 7. Leonardo Pisano Blgollo (a.k.a. Leonardo Fibonacci) 8. Isaac Newton and Wilhelm Leibniz 9. Andrew Wiles 10. Pythagoras